Impact of COVID-19 Governmental Restrictions on Emergency General Surgery Operative Volume and Severity. Issue 5 (May 2023) - Lund, Sarah; MacArthur, Taleen; Fischmann, Marianna Martini; Maroun, Justin; Dang, Johnny; Markos, James R.; Zielinski, Martin; Stephens, Daniel
Background: To describe the effect of the COVID-19 pandemic on emergency general surgery operative volumes during governmental shutdowns secondary to the pandemic and characterize differences in disease severity, morbidity, and mortality during this time compared to previous years. Methods: This retrospective cohort study compares patients who underwent emergency general surgery operations at a tertiary hospital from March 1st to May 31st of 2020 to 2019. Average emergent cases per day were analyzed, comparing identical date ranges between 2020 (pandemic group) and 2019 (control group). Secondary analysis was performed analyzing disease severity, morbidity, and mortality. Results: From March 1st to May 31st, 2020, 2.5 emergency general surgery operations were performed on average daily compared to 3.0 operations on average daily in 2019, a significant decrease ( P = .03). No significant difference was found in presenting disease severity, morbidity, or mortality between the pandemic and control groups. Discussion: This study demonstrates a decrease of 65% in emergency general surgery operations during governmental restrictions secondary to the COVID-19 pandemic. This decrease in operations was not associated with worse disease severity, morbidity, or mortality.